(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
ABSTRACT: This essay explores the intersection of religious symbols and judicial populism, focusing on the case-law related to the kirpan in Italy and Canada. In an era of rising populism, religious symbols become political tools, creating an “us-versus-them” narrative. The kirpan, a Sikh ritual dagger, can serve as a case-study for judicial populism, examining contrasting approaches in Italian and Canadian case-law. Italian case-law prioritizes public safety over religious freedom, while Canadian case-law adopts a nuanced approach, accommodating the wearing of the kirpan under some conditions. The kirpan’s legal ambiguity highlights the tension between religious freedom and public safety, reflecting the broader challenges of recognizing different identities in a multicultural society. SUMMARY: 1. Religious symbols, populism, and judicial populism - 2. Methodology and research questions - 3. The kirpan as a case-study for judicial populism - 4. Judicial populism in action: the Italian case-law - 5. Precautions against judicial populism: the Canadian case-law - 6. Countering judicial populism.